PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP NEGERI 4 PEKANBARU - Ratih Surya Pratiwi Surya Pratiwi; Titi Solfitri Solfitri; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research is student of class VIII.2 SMPN 4 Pekanbaru in the second semester academic years 2014/2015, which amounted to 34 students, consist of 13 boys and 21 girls. The research consisit of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of every cycle the quiz will be implemented. Data collection is done by observation and tests in the form of quiz. The result of research shows that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to quiz I and II. The number percentage of students who reach Minimum Mastery Criteria on basic, quiz I and II are respectively 67,65%, 79,41% and 79,41%. Results of this research indicates that appication of the learning model of Problem Based Learning can improve learning process and increase mathematics achievement from the students at class VIII.2 SMPN 4 Pekanbaru in the second semester academic years 2014/2015. Key Words: Mathematics Achievement, Problem Based Learning, Class Action Research